Notes on Early Land Plants Today. 44. Comments on sexuality in Solenostoma (Solenostomataceae, Marchantiophyta) and on some newly described taxa - Váňa, Jíri; Söderström, Lars; Hagborg, Anders; Von Konrat, Matt (Phytotaxa, 2013)
The sexuality of Solenostoma species is discussed and it is concluded that Solenostoma sanguinolentum is heteroicous. This and other morphological differences from Solenostoma marcescens are discussed and they are considered to belong to the same species. Heteroicity probably also occurs in Solenostoma micranthum and possibly in other Solenostoma species. Solenostoma rossicum and Solenostoma pyriflorum subsp. purpureum are new synonyms to Solenostoma sphaerocarpum. Solenostoma ochotense is a new synonym to Solenostoma hokkaidense. Solenostoma costaricanum is a new synonym to Solenostoma amoenum. Plectocolea subbalfourii is a new synonym to Solenostoma balfourii. Solenostoma rubrum var. underwoodii is a new synonym to Solenostoma rubrum. Plectocolea yunnanensis is a new synonym to Solenostoma sikkimense. Solenostoma inundatum var. grandirete is a new synonym to Solenostoma orbiculatum. Solenostoma kurilense and Solenostoma ovalifolia are new combinations and Solenostoma philippinense a new species.